Sexual Homicide in France - James, Jonathan (International journal of offender therapy and comparative criminology, 2019)
The primary objective of this study was to describe and compare the modus operandi, and associated contextual and situational factors, of French serial sexual murderers (SSMs) and nonserial sexual murderers (NSMs). A further objective was to verify the generalizability of the conclusions of James and Proulx's 2016 systematic review of the modus operandi of sexual murderers, the majority of whom were American or English. Detailed data on the precrime, modus operandi, postcrime, and victimology factors of 120 French sexual murderers (SSMs: n = 33; NSMs: n = 87) were compared. The results suggest that choice-structuring properties that shape the modus operandi of French sexual murderers are similar to those reported by James and Proulx: The modus operandi of French SSMs was shaped by homicidal, sadistic, and rape fantasies, while that of NSMs was shaped by the need to satisfy immediate, especially sexual, needs. However, it should be noted that while the modus operandi of American and English NSMs is primarily shaped by general deviance, that of French NSMs appear be primarily shaped by sexual deviance.